Antecedents of Brand Authenticity in Cause-Related Sport Marketing Campaigns - Keevan Statz; Brian Gordon (Journal of Applied Sports Management, 2025)
Cause-related sport marketing (CRSM) has been a popular managerial technique over the last two decades. There is a common perception that for CRSM to be effective, consumers must perceive the sponsoring brand to be authentic in its actions. Minimal empirical research has analyzed the antecedent factors that lead consumers to perceive a brand as authentic in CRSM. Using multiple linear regression, six antecedent factors’ impact on brand authenticity were tested. Perceptions of the brand’s motives and brand transparency were found to have a statistically significant impact on brand authenticity.
Keywords: cause-related sport marketing; brand authenticity; team identification; multiple regression